Cyclosporine Augments Hepatic Regenerative Response in Rats - KAHN, D. (1990)
A number of mechanisms participate in the hepatic injury that occurs during and following liver transplantation. A normal allograft regenerative response is probably essential for a successful transplant outcome. In this study, the effect of cyclosporine, a potent immunosuppressant used routinely after liver transplantation, on the regenerative response of the liver after partial hepatectomy was investigated. Male Wistar rats were pretreated for one week with either cyclosporine or the olive oil vehicle and were subjected to either a two-thirds partial hepatectomy or a sham operation. Animals were sacrificed at various times postoperatively and the remnant livers were weighed to determine the liver weight to body weight ratio, two biochemical measures of a regenerative response (cytosolic ornithine decarboxylase activity and thymidine kinase activity), and the hepatic content of estrogen and androgen receptors, as the content of these receptors has been shown to modulate, at least in part, the subsequent hepatic regenerative response. The preoperative hepatic cytosol content of ornithine decarboxylase, thymidine kinase, and estrogen receptor was significantly greater (P < 0.05) in rats pretreated with cyclosporine than in those treated with the vehicle alone. A significant increase in ornithine decarboxylase and thymidine kinase activities occurred after partial hepatectomy in both the cyclosporine-pretreated and vehicle-pretreated animals. The absolute levels for each parameter were also greater in the cyclosporine-treated animals than in the vehicle-treated controls at 24 hr after partial hepatectomy (P < 0.05). The pattern of change in the hepatic cytosolic content of estrogen and androgen receptors in both groups of animals was comparable with those described previously for regenerating liver. These data suggest that cyclosporine may predispose the liver to respond to either a regenerative signal or perceived need and thereby fortuitously enhance liver graft performance after successful surgical implantation.